21st Century Educational Leadership Skills That Impact Academic Administration Excellence in Educational Institutions at the Main City Educational Quality Development Network Level Under the Office of Phetchabun Primary Educational Service Area 2 - Trisean, Nattawut; Juntorn, Prachaub; Yordyot, Chatchavee (Journal for Developing the Social and Community, 2026)
Background and Aims: In the 21st century, social and technological changes have compelled school administrators to develop a wide range of skills to manage academic affairs effectively. The objectives of this study are: 1) to examine the 21st-century skills of school administrators at the Lakhmuang Academic Development Center under the Phetchabun Primary Educational Service Area Office 2; 2) to study the management of academic affairs toward excellence in schools under the same jurisdiction; and 3) to investigate the relationship between the 21st-century skills of administrators and the management of academic affairs toward school excellence at the Lakhmuang Academic Development Center under the Phetchabun Primary Educational Service Area Office 2. Methodology: This study is quantitative research. The sample consisted of 61 teachers and educational personnel from seven schools within the Lakhmuang Academic Development Network Center. Stratified random sampling was employed to select the participants proportionally. The research instrument was a questionnaire, and the data were analyzed using percentages, means, standard deviations, and multiple regression analysis. Results: The results of the study revealed that 1) the 21st-century skills of school administrators were at the highest overall level. When examined by specific dimensions, all aspects were rated at the highest level, with the highest mean scores observed in visionary leadership skills and technology and digital literacy skills. 2) The management of academic affairs toward school excellence was also at the highest overall level. All dimensions were rated at the highest level, with the highest mean scores found in instructional organization and assessment and evaluation. 3) The 21st-century skills of school administrators were positively and significantly related to the management of academic affairs toward school excellence at the 0.05 level, explaining 45.5% of the variance. Specifically, visionary leadership skills had a significant positive influence on the management of academic affairs toward school excellence at the 0.05 level. Conclusion: School administrators in the 21st century must possess a various of skills, including visionary leadership and digital technology proficiency, to manage academic affairs effectively. The study indicates that these skills play a crucial role in enhancing the management of academic affairs toward school excellence and provide a new framework for developing administrators in the digital era.